A Maqasid Al-Shari’ah based composite index to measure economic well-being in Malaysia - Adnan, Nasriyah; Ismail, Abdul Ghafar; Mohd Shafiai, Muhammad Hakimi; Md Ramli, Raudha (2023)
The study introduces an innovative composite index based on the principles of Maqasid Al Shariah to measure Malaysia's economic well-being. The Maqasid Economic Well-Being Index (MSEWI) represents a paradigm shift from traditional economic indicators by incorporating Islamic economic principles in assessing the country's overall economic well- being. In establishing MSEWI, the study has adhered to the five main objectives of the Maqasid al-Shari'ah scholars: the protection of faith, life, intellect, lineage, and property. This dimension is interpreted in the context of the modern economy and translated into measurable indicators. The initial results suggest that applying this index can lead to policies more aligned with the principles of Islamic justice, resulting in a more equitable distribution of wealth and an overall improvement in societal well-being. This study is specifically tailored to the economic context of Malaysia. While the methodology could be applied in other Muslim majority countries, its applicability and effectiveness may vary due to differences in cultural, social, economic, and legal frameworks. Conversely, like other index-based approaches, the (MSEWI) may have the potential drawback of oversimplifying complicated socio-economic circumstances. Although its purpose is to assess economic well-being comprehensively, some subtleties must be accurately reflected. Through MSEWI, this research contributes to a growing body of literature on Islamic economic metrics. It can influence policymaking in Malaysia and other Muslim-majority countries that seek economic justice through the lens of Islamic principles. This study represents one of the first attempts to integrate the principles of the Maqasid Al-Shari’ah directly into food security as a composite index for measuring economic well-being. The approach offers a new perspective on studying economic well-being from an Islamic worldview beyond conventional economic indicators.